2012
DOI: 10.1007/s10626-012-0151-1
|View full text |Cite
|
Sign up to set email alerts
|

Actuator saturation and anti-windup compensation in event-triggered control

Abstract: Event-triggered control aims at reducing the communication load over the feedback link in networked control systems by sending information only if certain event conditions, which guarantee a desired control performance, are satisfied. This article investigates the consequences of actuator saturation on the behavior of the event-triggered control loop in terms of its stability and information exchange. Stability properties are derived using linear matrix inequalities (LMIs) which show how the stability of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 29 publications
1
53
0
Order By: Relevance
“…Remark 2. Theorem 2 guarantees local stability of the origin while the results proposed in Kiener et al [2013] only guarantees the convergence of the closed-loop trajectories to a bounded set around the origin. Remark 3.…”
Section: Event-triggered Control Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Remark 2. Theorem 2 guarantees local stability of the origin while the results proposed in Kiener et al [2013] only guarantees the convergence of the closed-loop trajectories to a bounded set around the origin. Remark 3.…”
Section: Event-triggered Control Designmentioning
confidence: 99%
“…It is now well known that the presence of saturation may cause loss in performance, even unstable behavior (see, for example, Tarbouriech et al [2011] and references therein). At the knowledge of the authors, few results deal with event-based control and saturated system as in Kiener et al [2013]. In the current paper, extending the results developed in Seuret and Prieur [2011], we use the hybrid framework and the Lyapunov theory to define the update This work was was supported by ANR project LimICoS contract number 12 BS03 005 01.…”
Section: Introductionmentioning
confidence: 98%
“…There are few literatures studied event-triggered control with saturated inputs. In [18] and its follow-up work [19], the authors studied event-triggered output feedback control for linear systems with actuator saturation, where the practical stability is guaranteed. Then, they applied the anti-windup approach to improve the performance of the systems.…”
Section: Introductionmentioning
confidence: 99%
“…Few researchers address the setpoint tracking problem in the event-triggered control framework, see [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. An early approach of event-triggered PI control [7] has shown that the communication effort can be significantly reduced with little degradation of the control performance compared with the time-based counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…To prove asymptotic stability, an upper and lower bound on the inter-event time is considered. Taking the actuator saturation into account, stability analysis under absolute threshold policies is derived in [15,16], leading to a practical stability (ultimate boundedness). In addition to the setpoint tracking problem, the disturbance rejection problem is studied in [10,12,13] under absolute threshold policies.…”
Section: Introductionmentioning
confidence: 99%